Zum politischen Anspruch der Oral History. Über das epistemische Schweigen und die ontologische Taubheit der Mehrheitsgesellschaft - Immler, Nicole,Kovacs, Eva (SSOAR, GESIS – Leibniz-Institut für Sozialwissenschaften e.V., 2022)
Abstract: Listening is the art of those who practice oral history. But do we hear what we are told? And can we adequately (re)present the voices of those we have interviewed? In this article, we critically examine this implicit political claim of oral history with the help of empirical case studies. Using interview collections on Dutch (post)colonial history and on the history of Hungarian Roma, we show how the social phenomenon under investigation already became visible in the research situation itself, namely that life narratives of marginalized people were always dependent on the knowledge production by the majority. We explore the dynamics between interviewers and interviewees in order to clarify which framing allows us to (not) hear voices. We thus analyze the epistemic silence and the ontological
10.17169/fqs-22.2.3745
Keywords: (thesoz)Sinti und Roma; (thesoz)Framing-Ansatz; (thesoz)Methode; (thesoz)Interview; (thesoz)Ungarn; (thesoz)Oral History; (thesoz)Kolonialismus; (thesoz)Niederlande; Biografieforschung; Dutch colonial history; Framing; Hungary; Oral History; Roma genocide; Roma-Genozid; Ungarn; biographical research; epistemic injustice; framing; niederländische Kolonialgeschichte; oral history; othering; subaltern studies; Oral history; Postkolonialismus; Kolonialismus; Episteme; Vergangenheitsbewältigung